Pharmacologic Evidence of Green Tea in Targeting Tyrosine Kinases - Li, Joyce T.S.; Hon, Kam L.; Leung, Alexander K.C.; Lee, Vivian W.Y. (Current Reviews in Clinical and Experimental Pharmacology, 2021)
Background: Green tea has been extensively studied for its potential health benefits against diseases, such as cancers, cognitive degenerative diseases, and cardiovascular diseases. Methods: The authors undertook a structured search of peer-reviewed research articles from three databases including PubMed, Embase, and Ovid MEDLINE. Recent and up-to-date studies relevant to the topic were included. Results: Green tea extract exerts its functions by interacting with multiple signalling pathways in human cells. Protein tyrosine kinase is one of the examples. Abnormal activation of tyrosine kinase is observed in some tumour cells. Green tea extract inhibits phosphorylation, reduces expression, or attenuates downstream signalling of epidermal growth factor receptor, insulin-like growth factor receptor, vascular endothelial growth factor receptor, and non-receptor tyrosine kinase. Combination of green tea extract with tyrosine kinase inhibitors may provide synergistic effects by overcoming acquired resistance. Conclusion: Green tea extract can affect multiple receptor targets. In the current review, we discuss the pharmacological mechanisms of green tea on tyrosine kinases and their implications on common diseases.
Keywords: Cancer